Modeling inward foreign direct and indirect investment for Jordan: a comparative study - Al Eitan, Ghaith Naser (Curtin University, 2014)
The study aimed to identify the major determinants of inward foreign direct and indirect investment into Jordan and Australia. A comparative study was undertaken using advance econometric techniques in order to arrive at policy implications that may lead to increased foreign investment into Jordan. Country risk (financial health, economic health and political stability), trade openness, stock market price and macroeconomic data were analysed from 1996 to